Teori Hubungan Hukum Adat dan Pengaruhnya Terhadap Pembaharuan Hukum Islam Di Indonesia - Usqho, Mutia Urdatul; Firdaus, Beni; Endriyenti, Endriyenti (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
The development of customs and Islam became a harmonious relationship that should not have any overlap within it, but the theory imposed by the Dutch (Colonial) built the conception that customs and Islam could not be united with each other. So this can be made into a research study by explaining the theories presented by colonialism and evaluating them with the reforms of Islamic law in Indonesia. The goal is to find a bright spot between customs and Islam that has increasingly caused conflicts until now. The research was conducted using a literature study, which involved examining previous studies as primary sources and supplementing them with expert opinions to support existing theories. The results obtained show that customary law and Islamic law are openly stated to be very harmonious, but this is not the case when viewed from the three existing theories. However, the conception used, if revised, will become a renewal that indirectly illustrates that customary law also has Islamic concepts, and Islamic law can be aligned when there are things that contradict Islamic law.